2014
DOI: 10.3892/mmr.2014.2056
|View full text |Cite
|
Sign up to set email alerts
|

Ac-hE-18A-NH2, a novel dual-domain apolipoprotein mimetic peptide, inhibits apoptosis in macrophages by promoting cholesterol efflux

Abstract: A novel synthetic dual-domain apolipoprotein (apo)-mimetic peptide, Ac-hE-18A-NH 2 , has been proposed to possess several apo A-I-and apo E-mimetic properties. This study investigated the protective effect of this peptide on oxidized low-density lipoprotein (ox-LDL)-induced apoptosis in RAW264.7 cells. For this purpose, RAW264.7 cells were exposed to 50 µg/ml ox-LDL for 48 h, and then incubated with the peptide Ac-hE-18A-NH 2 at various concentrations. Apoptosis was detected using annexin V-fluorescein isothio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, in RAW264.7 macrophage-derived foam cells, the activation of autophagy ameliorates cholesterol accumulation through an ABCA1dependent pathway that mediates cholesterol efflux. Meanwhile, it is well documented that the accumulation of intracellular cholesterol is also crucial to induce macrophage apoptosis in vivo and in vitro [34,35]. Similar to our previous study [14], we found that autophagy activation is protective against luteolin-induced apoptosis in ox-LDL-induced macrophages.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, in RAW264.7 macrophage-derived foam cells, the activation of autophagy ameliorates cholesterol accumulation through an ABCA1dependent pathway that mediates cholesterol efflux. Meanwhile, it is well documented that the accumulation of intracellular cholesterol is also crucial to induce macrophage apoptosis in vivo and in vitro [34,35]. Similar to our previous study [14], we found that autophagy activation is protective against luteolin-induced apoptosis in ox-LDL-induced macrophages.…”
Section: Discussionsupporting
confidence: 89%
“…Concentrations of intracellular cholesterol were determined by kits as previously reported [ 28 ]. Protein pellets were solubilized in 1 M NaOH (Sinopharm Chemical Reagent Co., Ltd, Shanghai, China), and the protein concentration was determined using a BCA Protein Assay (Thermo Fisher Scientific Inc., Rockford, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The 18A peptide was one of the first mimetic peptides designed and evaluated for confirming the amphipathic helix hypothesis ( Table 1 ). Originally designed to characterize and study the behavior of amphipathic helices in nanodisc assembly [ 179 , 180 ], the 18A peptide also demonstrated anti-inflammatory properties [ 181 , 182 ]. For example, 18A was able to rapidly assemble with phospholipids into nanodiscs, solubilizing unilamellar vesicles and confirming the amphipathic helix hypothesis.…”
Section: The Era Of Hdl Mimetic Nanoparticles: Replenishing Hdl Quali...mentioning
confidence: 99%
“…They were shown to efflux cholesterol from macrophages and prevent monocyte adhesion to primary human endothelial cells. N and C terminal modifications with acetyl and amide groups were shown to enhance the lipophilicity and helicity of the peptide [ 181 ]. It was later renamed as 2F due to two phenyl alanine residues.…”
Section: The Era Of Hdl Mimetic Nanoparticles: Replenishing Hdl Quali...mentioning
confidence: 99%